Homeland. The complete fourth season [videorecording (DVD)] - Danes, Claire, 1979-; Patinkin, Mandy; Friend, Rupert; Choudhury, Sarita
In her new role as a CIA station chief, Carrie convinces Saul and Quinn to help her hunt down one of the world's most dangerous terrorists. But when Carrie recruits a young Pakistani as an asset, the lines between right and wrong blur and the operation spins out of control. Facing unclear loyalties at every turn, Carrie must take extreme measures and risk everything to protect her country.